Salat Jumat Daring dalam Perspektif Hukum Islam - Fakhrizal Idris; Muhammad Yusram; Azwar Iskandar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aims to: (i) know the valid requirements of Friday prayers; and (ii) analyze the validity of Friday prayers by online from the perspective of Islamic law. This research is qualitative descriptive research with library study techniques and theological-normative (syarâ€™Ä«) and philosophical approaches. The results of study show that: (i) Friday prayer is a mandatory worship based on the Qur'an, Sunnah and ijmak, which have the pillars and conditions that must be observed for the sake of validity; (ii) the implementation of Friday prayers y online is invalid. At least this can be reviewed from two aspects; first, aspects of the basic principles and objectives derived from Islamic sharia (maqÄá¹£id al-syarÄ«'ah), where keeping Friday prayers in accordance with the Sunnah of the Prophet Muhammad saw. became part of hifzu al-dÄ«n (keeping religion) so that it should not change the pattern of Friday prayer that the original law is a whole building. Islamic law has given rukhsah for every Muslim who is obliged to pray Friday prayer to replace it with Zuhr prayer when there is something that prevents it; second, the aspect of Islamic jurisprudence review, where Friday prayers require the existence of prayer congregations and is not validly performed individually. Analogizing online Friday prayers with online marriage contracts is incorrect because the law of qiyas must be analogous to the original law that has direct evidence and should not be to legal products or other qiyas results.